Inspecting PGC 165324 and PGC 977941 Galaxies Using a Combination ofPhotometric and Spectroscopic Methods - Ahmed, Abdullah K.; Al-baqir, Haydar R. (Iraqi Journal of Science, 2024)
Photometric and spectroscopic approaches were utilized to examine the two galaxies, PGC 165324 and PGC 977941. Data releases (DR7 and DR17) from "The Sloan Digital Sky Survey (SDSS)” were employed to acquire the observed data. Then, ellipsoids were fitted via employing the Image Reduction and Analysis Facility (IRAF) with utilising STSDAS Library, the ELLIPS task. Along with the astrometric characteristics, the surfaces’ brightness of the galaxies PGC 165324 and PGC 977941, as well as their magnitudes, cumulative flux, central axis position angles, ellipticities, vertical and horizontal shifts, isophotal shape variables (B4), and also the star-forming rates (SFRs), were analysed and evaluated. It was indicated that the two galaxies, are members of a close pair galaxy system; in addition, they are considered a physical system; the PGC 165324 galaxy was a merging galaxy with a higher SFR. It was likely that the PGC 977941 had separated itself from the galaxy collision and drifted away.